The Role of Cardiotocography in Obstetric Practice: Maternal and Fetal Safety - Jumayeva Durdona (American Journal of Bioscience and Clinical Integrity, 2024)
Cardiotocography (CTG) is a modern method of assessing the state of the fetus by the nature of the heartbeat. CTG is performed only in the third trimester of pregnancy, more precisely after the 32nd week, because only after this period does the relationship between the contraction of the fetal heart and its functional state appear. Cardiotography is prescribed for timely diagnosis of fetal diseases, which allows the obstetrician-gynecologist to prescribe the correct treatment, evaluate its effectiveness and, if necessary, admit the pregnant woman to the maternity hospital, where the optimal time and method are determined. delivery is determined based on the results of CTG, ultrasound and Doppler measurements.